VIDEO DOKUMENTER DAMPAK POLA ASUH TOXIC PARENTS TERHADAP KESEHATAN MENTAL REMAJA GEN Z - Aptianopa Nur, Mochammad; Agusta, Aldrian (AKSA: Jurnal Desain Komunikasi Visual, 2024)
A healthy and harmonious relationship is essential for creating warmth within a family. However, the quality of interaction between parents and children is often overlooked, which can significantly impact a child's mental health and habits. A lack of effective communication and understanding of appropriate parenting approaches can affect this relationship, especially in the child’s emotional development. This documentary aims to raise public awareness, particularly among parents, about the effects of less harmonious parent-child relationships on the mental health of teenagers. The documentary seeks to rekindle the feelings of love, safety, and warmth experienced in childhood for teens facing these challenges. Presented from three perspectives—children, parents, and psychologists—this documentary provides neutral, balanced, and comprehensive information. As an effective medium, it is expected to bring this important issue to the public, especially in educating parents and teenagers about the impact of toxic parenting on children's mental health.